2019
DOI: 10.1242/dmm.037630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pathologies of bone fracture modelled in zebrafish

Abstract: Reduced bone quality or mineral density predict susceptibility to fracture and also attenuate subsequent repair. Bone regrowth is also compromised by bacterial infection, which exacerbates fracture site inflammation. Because of the cellular complexity of fracture repair, as well as genetic and environmental influences, there is a need for models that permit visualisation of the fracture repair process under clinically relevant conditions. To characterise the process of fracture repair in zebrafish, we employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 82 publications
4
64
0
Order By: Relevance
“…Zebrafish are also a useful model for fracture repair studies as they show a fracture healing response with callus formation which is very similar to mammals (Sousa et al 2012 ; Tomecka et al 2019 ). Using the GFP-Map1Lc3 line and the live bone stain, Alizarin red, we were able to perform a fin fracture assay which showed that the expression of Map1Lc3 increases during the early stages of fracture repair (Fig.…”
Section: Current Tools Available To Study Autophagy In Zebrafishmentioning
confidence: 99%
“…Zebrafish are also a useful model for fracture repair studies as they show a fracture healing response with callus formation which is very similar to mammals (Sousa et al 2012 ; Tomecka et al 2019 ). Using the GFP-Map1Lc3 line and the live bone stain, Alizarin red, we were able to perform a fin fracture assay which showed that the expression of Map1Lc3 increases during the early stages of fracture repair (Fig.…”
Section: Current Tools Available To Study Autophagy In Zebrafishmentioning
confidence: 99%
“…Dedifferentiation of mature osteoblasts also occurs during repair of zebrafish fin fractures and skull injuries . While osteoblast dedifferentiation is more limited in mammals, fin repair after fracture exhibits some similarities to mammalian long bone fracture, including formation of a remodeling callus, and recruitment of osteoclasts . Recently, it was shown that neutrophils dynamically colonize the fracture site.…”
Section: Formation and Integration Of The Zebrafish Musculoskeletal Smentioning
confidence: 99%
“…Recently, it was shown that neutrophils dynamically colonize the fracture site. When infected with Staphylococcus aureus , neutrophils were retained in the fracture site and repair was reduced . Further studies examining the utility of the fin fracture model to study the aspects of fracture biology are warranted.…”
Section: Formation and Integration Of The Zebrafish Musculoskeletal Smentioning
confidence: 99%
“…and WT fish as has been previously described (Geurtzen et al, 2014;Tomecka et al, 2019). Injured fish 91 were stained with calcein at different timepoints to monitor calcification of newly formed bone matrix in 92 the callus.…”
Section: Introduction 28mentioning
confidence: 99%